Refleksi Pengamalan Tasawuf di Aceh pada Abad ke-19M dalam Kitab Dia’ul Wara' - Fakhriati Fakhriati (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
Historically, it is proved that the coming of Islam into Aceh went on together with teaching and applying sufism. For the next term, sufism then internalized in Achenese life. Thus, there are many ulamas who mastered and taught sufism. They had left valuable heritage through their writing called manuscripts which can be used by the people, both in their era and the next generation. One of the sufi ulamas who left his writing works is Teungku Khatib Langgien arrived from Langgien, Pidie Regency. One of his works which is important is ¬i±’ul War± contained of sufi doctrines. Teungku Khatib Langgien can be catagorized as a wise ulama in discussing and teaching his people. He concerned their ability in understanding his teaching. In his book, I argue that the information inside is able to be read by any level of people and used in any time without limitted time.Keywords: sufism, manuscripts, Aceh, and ulama